Impact of pomegranate extracts on longevity and wing fluctuating asymmetry in Drosophila melanogaster: a geometric morphometric analysis - Vijay Kumar Rajashekhar; Belgaum Sridhar Srinath; Shivanna Nanjaiah (نامه انجمن حشره‌شناسی ایران)
Longevity plays a significant role in determining an animal's overall health. Nutrition is a key factor that can influence an animal's longevity. Studying the relationship between wing symmetry and longevity provides a useful approach to understanding how nutrition can affect both longevity and symmetry. The effect of Pomegranate Juice (PJ) and Pomegranate Peel (PP) on longevity and Fluctuating Asymmetry (FA) of wings in male and female Drosophila melanogaster was analysed using Geometric Morphometric Analysis (GMA). The study revealed that PJ and PP-treated flies showed increased longevity and the highest FA compared to control in both males and females. Between PJ and PP-treated flies, PJ had the highest longevity in both males and females whereas PP flies had higher FA in both sexes. Between the sexes, females had lower longevity and FA values compared to males. Overall GMA study reveals shape variation for wings and the presence of a strong FA in PJ and PP flies. Pearson correlation revealed a strong positive association between longevity and wing FA.